Responsible Muslims and Normalizing Islam. (5th May 2022) - de Koning, Martijn
Abstract : In this article, I take up the "Muslim Question" in relation to neoliberalism and the Dutch government through a community approach focusing on the responsibilization of citizens. Based on fieldwork that I have conducted over the last 15 years, I will argue that, in order to understand the Muslim Question, we have to explore how Muslims respond to the "neo-liberal Muslim Question." I will explore how the paradoxes and tensions that co-constitute the neoliberal Muslim Question, create opportunities for some Muslims to be able to find, then enlarge and navigate a space for themselves as responsible subjects within a particular framework which also, simultaneously, targets them as potentially unruly subjects. In doing so I show how Muslims engage with the neoliberal governance of themselves and demonstrate how their approach is informed, shaped, enabled and challenged by the racial neo-liberal discourse of the Muslim Question.